Defining the Optimal Level of Pressure Fluctuations at Pressure Control Management Strategy for Reducing Water Losses in Water Networks - Talha İbrahim Arduçoğlu; Furkan Boztaş; Mahmut Fırat (Doğal Afetler ve Çevre Dergisi)
A significant rate of the physical losses in networks are caused by unreported leaks. Leaks are directly related to pressure, and many public institutions and researchers are conducting management studies on pressure parameters. Pressure management methods are classified as classical and advanced pressure management. Many studies conducted worldwide have enabled the minimization of operating pressure. In this study, the hourly pressure difference was selected as the parameter to be minimized during the pressure management study, and it was aimed to minimize the pressure fluctuations of the network during the day. The data of the working networks, the hydraulic model of which was created in the EPANET program, was transferred to the MATLAB environment with the EPANET-MATLAB Toolkit. First, the network was analyzed with classical pressure management. In the next stage, the operating scenario for the flow-sensitive advanced pressure management was started to be created. Genetic algorithm was used in the MATLAB environment to create the most suitable scenario. Inlet pressure was selected as the optimization variable. The sum of the hourly pressure change differences of the network during the day was selected as the objective function. As a result of the optimization, the average pressure fluctuations in the working area were reduced by 55% from 18.56 m to 8.41 m. In addition, the average pressure of the network was reduced from 48.2 m to 37.3 m.